Intimate partner violence and maternal health services utilization: evidence from 36 National Household Surveys - Jessica Leight; Nicholas Wilson (BMC, 2021)
Abstract Background High rates of maternal mortality and intimate partner violence (IPV) are both major worldwide health challenges. Evidence from single-country samples suggests that IPV may be an important risk factor for low utilization of maternal health services, but there is little large-scale evidence on this association. This paper evaluates whether IPV is a risk factor for low utilization of maternal health services in a large cross-country sample, and also compiles evidence on the relative effects of different forms of IPV. Methods We analyze the association between intimate partner violence and utilization of maternal health care, using a dataset compiling all Demographic and Health Surveys that report data on intimate partner violence. Using data on 166,685 women observed in 36 countries between 2005 and 2016, we estimate logistic regression models to analyze the relationship between lifetime experience of IPV and utilization of antenatal care (ANC), facility delivery care, and postnatal care. We estimate both unadjusted models and models adjusted for geographic and sociodemographic characteristics that are generally correlated with utilization of maternal health care (including age, education, number of children, wealth status, marital status, and urbanity). Results Lifetime experience of any IPV is associated with decreased use of maternal health services in a broad sample of births observed in lower and middle-income countries: in particular, the utilization of four or more ANC visits, the number of ANC visits, and the utilization of facility care at birth. This association remains statistically significant even after adjusting for country of residence, subnational region of residence, and additional individual-level covariates; however, there is no statistically significant association between experience of any IPV and postnatal care. The only form of IPV significantly associated with care utilization is physical IPV. Conclusions Women experiencing physical intimate partner violence show lower levels of utilization of maternal health services in a large sample of developing and middle-income countries. Given that reduced utilization of maternal health services is correlated with maternal and neonatal health outcomes, this pattern suggests that IPV prevention may be an important component of interventions targeting enhanced maternal and neonatal health.